Droplet digital PCR of serum miR-499, miR-21 and miR-208a for the detection of functionally relevant coronary artery disease. (15th January 2019) - Hortmann, M.; Walter, J.E.; Benning, L.; Follo, M.; Mayr, R.M.; Honegger, U.; Robinson, S.; Stallmann, D.; Duerschmied, D.; Twerenbold, R.; Badertscher, P.; du Fay de Lavallaz, J.; et al.
Abstract: Background: microRNAs (miRNAs) have shown promise as potential new biomarkers for myocardial injury and myocardial ischemia. New digital polymerase chain reaction (PCR) techniques allow for highly precise and reliable absolute direct quantification. Methods: In this pilot study we used droplet digital PCR (ddPCR) to assess if miRNAs might be released into circulation in patients with functionally relevant coronary artery disease (CAD). Blood samples for measurement of high-sensitivity cardiac troponin I (hs-cTnI) and miRNAs were obtained before, immediately after peak stress, and 2 h after stress testing in a blinded manner in consecutive patients referred for rest/stress myocardial perfusion single-photon emission tomography/computer tomography (MPI-SPECT/CT). ddPCR was used to directly quantify the serum concentrations of miR-21, miR-208a, and miR-499 as potential markers of myocardial injury/ischemia. Functionally relevant CAD was determined by expert interpretation of MPI-SPECT/CT, coronary angiography and fractional flow reserve, if performed. Results: Overall, 200 patients were included and functionally relevant CAD was detected in 85 of them (42%). Neither miR-21, miR-208a, nor miR-499 concentrations differed at rest, stress, or 2-h after stress when comparing patients with versus without functionally relevant CAD, while hs-cTnI concentrations were significantly higher in patients with functionally relevant CAD (P < 0.001). Exercise-induced changes in miRNA or hs-cTnI concentrations did not have diagnostic utility and were similar in patients with versus without functionally relevant CAD. Conclusion: miR-208a, miR-21 and miR-499 concentrations at rest, after exercise and exercise-induced changes do not provide additional clinical value regarding the detection of functionally relevant CAD. Highlights: miR-208a, miR-21 and miR-499 concentrations at rest do not provide clinical value for the detection of functionally relevant CAD. miR-208a, miR-21 and miR-499 concentrations after exercise and exercise-induced changes do not provide clinical value for the detection of functionally relevant CAD. miR-208a, miR-21 and miR-499 do not predict all-cause mortality or the occurrence of MACE during long-term follow-up.